Popularity Of Da'wah Ustad Muhammad Ihsan As A Young Da'i Through Youtube Accounts In Lombok - Heri, Heriyadi; Siti Nurul Yaqinah (Universitas Islam Negeri (UIN) Mataram, 2024)
Almost all da'I today appear active in preaching on social media, including Youtube, Instagram, Facebook, and Twitter. Several national preachers are already popular in Indonesia, namely Ustad Abdussomad, Ustad Syam, Ustad Hadi Hidayat, and Gus Baha'. Local preachers, such as TGH Muammar Arafat, TGH Mukhlis Ibrahim, and Dr. TGH Zainudin Abdul Majid, are also popular for da'wah. Today, another young preacher is popular in society; the source of his Popularity comes from the theme of preaching, methods of preaching, and social media accounts. Ustad Muhammad Ihsan fa, familiarly known as Ustad Ocet, is a young preacher from Lombok who is popular today. So, researchers want to explore the Popularity of Ustad Muhammad Ihsan's Da'wah through his Youtube account. This research uses the Net Nography method, an ethnographic approach, to analyze social interactions in cyberspace. Researchers focused on looking for data related to Ustad Muhammad Ihsan's preaching content on several Youtube accounts using steps such as Identifying social network platforms, collecting data, analyzing data using specific qualitative analysis methods, content analysis, and interpretation and conclusions from all data. The results of this research show that the Popularity of Ustad Muhammad Ihsan's preaching as a Young Da'I through his Youtube account in Lombok is proven by several things such as First, He is still young but has the skills to preach. Second, have a friendly attitude. Third, many Youtube channels upload lecture videos. Fourth, using interesting da'wah methods such as the humorous da'wah method, the communicative da'wah method, the singing da'wah method, and the storytelling da'wah method.